The Effect of Corporate Governance Mechanism on Company Value with Company Performance as Intervening Variable - ADILA, NUR; Arifin, Zaenal (Archives of Business Research, 2021)
Corporate Governance is a system that regulates and controls a company which expected to give and increase Company Value to investors. With the existence of Corporate Governance, it is expected that Company Performance will give a good influence on the company. One of the cases is after Indonesia went through a prolonged crisis since 1998, the repairing process in the companies took a long time and it is caused by the weakness of Corporate Governance application in the companies, which will affect the companies’ performance and decrease the companies’ values. The purpose of this research is to analyze the effects of the Corporate Governance mechanism on Company Value with Company Performance as an intervening variable. The case study used in this research is the companies included in IDX BUMN 20 Tahun 2020 list. The result of this study is that Independent Commissioner doesn’t affect values and Company Performance, the board of directors affects Company Value positively, the board of directors doesn’t affect Company Performance. The Audit Committee doesn’t affect the Company Value. The Audit Committee affects the Company Performance positively. The Company Performance is not capable to mediate the independent commissioner’s effect on Company Value. The Company Performance can mediate the effect of the Board of Directors on the Company Value, the Company Performance can’t mediate the effect of Audit Committee on the Company Value.